Expanding the molecular and clinical phenotypes of FUT8‐CDG. Issue 4 (23rd February 2020) - Ng, Bobby G.; Dastsooz, Hassan; Silawi, Mohammad; Habibzadeh, Parham; Jahan, Shima B.; Fard, Mohammad A. F.; Halliday, Benjamin J.; Raymond, Kimiyo; Ruzhnikov, Maura R. Z.; Tabatabaei, Zahra; Taghipour‐Sheshdeh, Afsaneh; Brimble, Elise; et al.
Abstract: Pathogenic variants in the Golgi localised alpha 1, 6 fucosyltransferase, FUT8, cause a rare inherited metabolic disorder known as FUT8‐CDG. To date, only three affected individuals have been reported presenting with a constellation of symptoms including intrauterine growth restriction, severe delays in growth and development, other neurological impairments, significantly shortened limbs, respiratory complications, and shortened lifespan. Here, we report an additional four unrelated affected individuals homozygous for novel pathogenic variants in FUT8. Analysis of serum N ‐glycans revealed a complete lack of core fucosylation, an important diagnostic biomarker of FUT8‐CDG. Our data expands both the molecular and clinical phenotypes of FUT8‐CDG and highlights the importance of identifying a reliable biomarker for confirming potentially pathogenic variants.